Modern pharmacological strategies in the treatment of Drug-Resistant Epilepsy: evaluation of efficacy and safety: a review - Kuna, Wojciech; Niski, Jakub; Pietrucha, Jakub Mateusz; Rutkowska, Anna; Lichoń, Jakub Michał; Gołdyn, Mateusz Józef; Kuna, Paweł Jan; Turczynowski, Kamil Igor; Chojniak, Alicja Katarzyna; Turczynowski, Konrad Olaf (Quality in Sport, 2026)
Drug-resistant epilepsy (DRE) is a neurological condition, defined as a failure to make the patient seizure free, after the use of two tolerated, appropriately chosen antiepileptic drugs (AED). Although there is an increasing number of available antiepileptic drugs, it is estimated that pharmacotherapy remains ineffective in approximately 30% of patients. Drug-resistant epilepsy is considered as one of the greatest challenges in modern neurology that affects millions of patients worldwide, who do not respond to standard treatments. Even though epilepsy is one of the most common neurological diseases, with a global total of 50 million people suffering from the condition, treatment of its resistant forms remains complicated and often ineffective. Chronic epileptic seizures can cause serious health problems, limiting patients' mobility, affecting quality of life and increasing the risk of emotional disorders such as depression and anxiety. In response to this challenge, the development of modern drugs for drug-resistant epilepsy has become a medical priority. In recent years, there has been growing interest in new medications such as Cenobamate, Fenfluramine and Cannabidiol, which have different mechanisms of action and promising results in reducing the seizure frequency. Before diagnosing DRE, it is essential to exclude the pseudo-resistance, which may result from different factors such as inadequate doses of medicine, choosing the incorrect medications, or patient-related errors (poor compliance).